Design, Development, and Characterization of Modified Xanthan Gum Based Novel in situ Gel of Ciprofloxacin Hydrochloride for Ophthalmic Drug Delivery (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: Ciprofloxacin hydrochloride is a broad-spectrum a powerful fourth generation fluoroquinolone antibioticactive against both Gram-positive and Gram-negative ocular pathogens such as Pseudomonas aeruginosa andStaphylococcus aureus and used the treatment of ocular infections. In conventional dosage forms its washout, poorretention, drainage from eyes affects its therapeutic efficiency, so there is need of novel formulation of it. The aimand objectives of this research work are to explore the applicability of our previously modified xanthan gum informulation, optimization, and evaluation of in situ gel of ciprofloxacin hydrochloride for ophthalmic drug delivery.Materials and Methods: Fourier-transform infrared (FT-IR) and differential scanning calorimetry (DSC) study wasperformed to find out compatibilities between drug and polymers. To find out the impact of Conc. of ModifiedXanthan Gum …(X1) and… HPMC (X2) on dependent variables, i.e., gelation temperature and viscosity 32 factorialdesigns Optimization technique was used. In situ gel was prepared using modified xanthan gum and HPMC, etc. Theprepared in situ gel of ciprofloxacin was evaluated for pH, gelation time, gelation temperature, viscosity, drug content,syringeability, antimicrobial potential, and in vitro drug release. Results and Discussion: FT-IR and DSC studysuggests no interaction between ciprofloxacin, modified xanthan gum, and HPMC. The pH of in situ gel solutionwas found to be around 6.6 ± 0.2–6.9 ± 0.08 which is an acceptable range for ophthalmic preparations. Gelation timeof prepared in situ gel solution was found to be around 10.6 ± 1.2–32 ± 0.8 s. Gelation temperature of prepared insitu gel batches was found to be around 30.6 ± 0.4–35 ± 0.8°C. It was found that increasing the concentration of thepolymer resulted in a significant increase in viscosity. Modified xanthan gum had a more pronounced effect on theviscosity than HPMC at the studied ranges. In vitro, drug release studies showed a polymer concentration-dependentdecrease in drug release. Formulation F8 selected as an optimized batch has maximum gelling temperature 34.6 ±1.2°C and minimum drug release 91.59% drug release. Optimized formulation gave satisfactory results in terms ofantimicrobial activity. The optimization study was successfully conducted using 32 factorial designs. Conclusion:Developed in situ gelling systems are viable alternative to conventional ophthalmic products with added benefits ofsustained drug released and it will promising approach toward the treatment of various bacterial infections.